AB0453 Response to TOCILIZUMAB in Rheumatoid Arthritis is not Influenced by the Body Mass Index of the Patient. (10th June 2014) - Pers, Y.-M.; Godfrin-Valnet, M.; Lambert, J.; Fortunet, C.; Constant, E.; Mura, T.; Pallot-Prades, B.; Jorgensen, C.; Maillefert, J.-F.; Marotte, H.; Wendling, D.; Gaudin, P.
Abstract : Objectives: To assess relationship between body mass index (BMI) and efficacy of tocilizumab (TCZ) in rheumatoid arthritis (RA) patients. Methods: We conducted a retrospective study of the use of TCZ in patients with RA followed by five academic hospitals in France. The efficacy of TCZ was evaluated at 6 months by the European League Against Rheumatism (EULAR) response. Univariate and multivariate logistic regressions were performed adjusting for age, sex, disease duration, C-Reactive protein, erythrocyte sedimentation rate, presence of erosive lesions, rheumatoid factor and anti-citrullinated peptide antibodies positivity, disease duration, disease activity score, concomitant therapy by disease modifying anti-rheumatic drugs. Results: Among 222 RA patients treated by TCZ, 58.5% had a low BMI<25kg/m 2, 26% had an intermediate BMI between 25-30kg/m 2, and 15.5% had a high BMI>30kg/m 2 . No significant association between BMI and response to TCZ at 6 months was found after adjustment for potential confounding factors (OR 0.47; 95%CI [0.18; 1.23], p=0.12 and OR 1.56 95%CI [0.42; 5.67], p=0.49 for BMI=25-30kg/m 2 and BMI>30kg/m 2 respectively compared to BMI<25kg/m 2 ). Conclusions: Response to TCZ in RA patients is not influenced by the baseline BMI, in contrast to anti-TNF drugs. Future research should assess these differences prospectively for better comparisons. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1508